2011
DOI: 10.1080/17461391.2010.500335
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of endurance exercise on jumping and kicking performance in top‐class young soccer players

Abstract: The aim of this study was to examine the acute effects of endurance exercise on jumping and kicking performance in young soccer players. Twenty-one top-class young soccer players (16.1 +0.2 years) performed a countermovement jump test and a maximal instep soccer kick test before and after running for 20 min on a treadmill at 80% of their individual máximum heart rate. Two forcé platforms were used to obtain the following parameters during the countermovement jump: jump height, máximum power, máximum power rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
3
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 27 publications
(35 reference statements)
3
17
3
10
Order By: Relevance
“…The values reported were also greater than the values reported by Orloff et al (2008) in amateur players and similar to values reported by Juarez et al (2011) in elite youth players. The ground reaction forces are almost three times the body weight, and this greater force perhaps contributes to a greater ball velocity in professional soccer players.…”
Section: Figure 16: Peak Hip Velocities (M/s) Compared Across Previoucontrasting
confidence: 45%
See 4 more Smart Citations
“…The values reported were also greater than the values reported by Orloff et al (2008) in amateur players and similar to values reported by Juarez et al (2011) in elite youth players. The ground reaction forces are almost three times the body weight, and this greater force perhaps contributes to a greater ball velocity in professional soccer players.…”
Section: Figure 16: Peak Hip Velocities (M/s) Compared Across Previoucontrasting
confidence: 45%
“…The kicking motion is a sequential motion, beginning at the hip and going down to the foot, with each joint attaining a maximal velocity from proximal to distal segments in the same order ( Figure 17) (Juarez et al, 2011;Lees & Nolan, 1998). Keeping this pattern in mind, and looking at Table 20, one can say that a previous hamstring injury affects the dominant limb knee from reaching maximal velocities (previously uninjured dominant knee velocity = 9.53 ± 0.91 m/s and previously injured dominant knee velocity 9.00 ± 0.87 m/s) which consequently led to differences in the ball velocities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations